Cdt1 overexpression drives colorectal carcinogenesis through origin overlicensing and DNA damage. Issue 1 (9th November 2022) - Petropoulos, Michalis; Champeris Tsaniras, Spyridon; Nikou, Sofia; Maxouri, Styliani; Dionellis, Vasilis S; Kalogeropoulou, Argyro; Karamichali, Angeliki; Ioannidis, Konstantinos; Danalatos, Iosif‐Rodolfos; Obst, Mandy; Naumann, Ronald; Delinasios, George J; et al.
Abstract: Chromatin licensing and DNA replication factor 1 (CDT1), a protein of the pre‐replicative complex, is essential for loading the minichromosome maintenance complex (MCM) helicases onto the origins of DNA replication. While several studies have shown that dysregulation of CDT1 expression causes re‐replication and DNA damage in cell lines, and CDT1 is highly expressed in several human cancers, whether CDT1 deregulation is sufficient to enhance tumorigenesis in vivo is currently unclear. To delineate its role in vivo, we overexpressed Cdt1 in the mouse colon and induced carcinogenesis using azoxymethane/dextran sodium sulfate (AOM/DSS). Here, we show that mice overexpressing Cdt1 develop a significantly higher number of tumors with increased tumor size, and more severe dysplastic changes (high‐grade dysplasia), compared with control mice under the same treatment. These tumors exhibited an increased growth rate, while cells overexpressing Cdt1 loaded greater amounts of Mcm2 onto chromatin, demonstrating origin overlicensing. Adenomas overexpressing Cdt1 showed activation of the DNA damage response (DDR), apoptosis, formation of micronuclei, and chromosome segregation errors, indicating that aberrant expression of Cdt1 results in increased genomic and chromosomal instability in vivo, favoring cancer development. In line with these results, high‐level expression of CDT1 in human colorectal cancer tissue specimens and colorectal cancer cell lines correlated significantly with increased origin licensing, activation of the DDR, and microsatellite instability (MSI). © 2022 The Pathological Society of Great Britain and Ireland.